Java2Sequence: a tool for the visualization of object-oriented programs in introductory programming - Barros, João Paulo (2013)
This poster presents a Java based visualization tool for introductory object-oriented courses. The tool generates UML Sequence Diagrams from the execution of Java programs. The generated diagrams are enriched with a set of textual annotations that facilitate comprehension as they "connect" code and the respective diagrammatic representation.